Focal adhesions: a personal perspective on a half century of progress. (30th August 2017) - Burridge, Keith
Abstract : Focal adhesions (FAs) are specialized sites within the cell where clustered integrin receptors interact with the extracellular matrix on the outside of cells and with the actin cytoskeleton on the inside. They provide strong adhesion to the matrix and transmit mechanical tension generated within cells across the plasma membrane to the external environment. Additionally, they act as scaffolds for many signaling pathways triggered by integrin engagement or mechanical force exerted on cells. Here I describe my personal perspective on FA research which I have witnessed since the initial discovery and description of FAs as electron dense regions of the ventral plasma nearly half a century ago. Abstract : A REF52 fibroblast, plated on a collagen‐coated glass coverslip, reveals focal adhesions stained for vinculin (green), F‐actin (red) showing stress fibers, and the nucleus labeled in blue. In this Discovery‐in‐Context Review, Keith Burridge provides a personal account on focal adhesion research since its initial discovery and description nearly half a century ago.